Cost-effectiveness of polysomnography in the management of pediatric obstructive sleep apnea. (June 2020) - Mitchell, Margaret; Werkhaven, Jay A.
Abstract: Objectives: At our institution, younger children require polysomnography (PSG) testing to confirm obstructive sleep apnea (OSA hereafter) before surgical intervention by adenotonsillectomy (T&A). Given that sleep studies can be costly, we investigated the cost-effectiveness of PSG as well as the possible role for symptom documentation in evaluation for T&A. Methods: Pediatric patients age 1–3 years who received PSG testing between Jan. 2015 and Jan. 2016 who had not previously had T&A were identified for retrospective cost analysis. Cost data were obtained from institutional accountants. We defined a positive PSG as obstructive apnea-hypopnea index ≥1. Logistic regression analysis was used, and statistical significance was set a priori at p < 0.05. Sensitivities and specificities of symptom documentation screen for OSA were compared to gold standard, or PSG testing. Results: Of the 176 children who received polysomnography testing, 140 (80%) had a positive PSG indicative of OSA. Seventy-one (51%) children with OSA underwent T&A within 1 year of PSG, and 10 (7%) eventually received T&A after 1 year from PSG date. Of the children whose PSG results were negative (n = 36), 14 (39%) still underwent T&A within 1 year (n = 7, 19%) or later (n = 7, 19%). Children with positive sleep studies were significantly more likely to receive T&A within one year of PSG (p = 0.0006) and at any time after PSG (p = 0.04). Hospital costs for T&A varied widely while PSG costs were fairly consistent. Using average institutional costs of T&A and PSG, the total cost of a T&A was 17.7× the cost of PSG testing. Using number of recorded symptoms to diagnose OSA instead of PSG testing yielded low specificities. Conclusion: Fifty-eight percent of patients with OSA and 39% of patients without OSA had a T&A within 1 year or later, although positive PSG was significantly associated with a higher likelihood of receiving T&A. Given costs at this institution and current decision-making practices, 147 PSGs would need to be done to account for the cost of one T&A, which in our cohort would occur after approximately 305 days.